Analisis Sistem Rekrutmen dan Seleksi yang Berimplikasi Pada Kinerja Karyawan: Study Kasus pada PT Mega Auto Central Finance - Rendy Renaldi; Reniza Helena Putri (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Human Resource (HR) plays a crucial role in the success of organization. The recruitment and selection system at PT Mega Auto Central Finance and its impact on employe performance. The research employs a qualitative approach with interview as the primary method to understand the selection process. The findings indicate that PT MEGA AUTO CENTRAL FINANCE has implemented a system that considers job performance, personal traits, and work behavior when selecting candidates. However there are some recommendations for improvement. First, concerning the recruitment system, the company can diversify its sources for recruiting employes by collaborating with educational institutions and online platform. Second, in the selection proses, the company needs to enhance objectivity and diversity by ensuring that assessment are based on relevant competencies and qualifications while considering the diversity of the candidates being evaluated. These improvements are expected to strengthen employees’ contribution to the company’s goals. Thus, this research provides at better understanding of the importance of and effective recruitment and selection system in supporting organizational performance.